Roberto d’Aubuisson vs Schafik Handal: Militancy, Memory Work and Human Rights - Sprenkels, Ralph (European Review of Latin American and Caribbean Studies, 2011)
This article examines the memory work that former parties to the Salvadoran conflict engage in with regard to two key historical leaders: Roberto d’Aubuisson, on the right, and Schafik Handal, on the left. In spite of the peace process’ relative success, El Salvador continues to be politically divided. Narratives concerning the historical role of these two leaders and their respective organizations are mobilized frequently and emphatically in political activities. The two main partisan groups strive to glorify their past and discredit that of their adversaries by use of ‘militant memories’. Building on theory regarding memory politics, the article analyses how rhetorical requirements associated with militant politics propagandize history to nurture loyalty, polarization and even impunity. Resumen: Roberto d’Aubuisson contra Schafik Handal: Militancia, Construcción de la Memoria y Derechos HumanosEn este artículo se examina el trabajo sobre la memoria que realizan las antiguas partes del conflicto salvadoreño con respecto a dos líderes históricos claves: Roberto d’Aubuisson, de derechas, y Schafik Handal, de izquierdas. Pese al relativo éxito del proceso de paz, El Salvador sigue estando políticamente dividido. Representaciones respecto al papel histórico de estos dos líderes y sus respectivas organizaciones son frecuente y enfáticamente introducidas en actividades políticas. Los dos principales partidos se esfuerzan por ensalzar su propio pasado y desacreditar el de sus adversarios mediante el recurso a ‘memorias militantes’. Estudiando las teorías sobre las políticas de la memoria, en el artículo se analiza cómo las exigencias retóricas asociadas con las políticas militantes transforman la historia en propaganda para alimentar la lealtad, la polarización e incluso la impunidad.